Accessing Economic and Political Impacts of Hydrological Variability on Treaties : Case Studies on the Zambezi and Mekong Basins - Blankespoor, Brian; Basist, Alan; Dinar, Ariel; Dinar, Shlomi (2012)
International river basins will likely face higher hydrologic variability due to climate change. Increased floods and droughts would have economic and political consequences. Riparians of transboundary basins governed by water treaties could experience non-compliance and inter-state tensions if flow falls below levels presumed in a treaty. Flow information is essential to cope with these challenges through water storage, allocation, and use. This paper demonstrates a simple yet robust method, which measures gauge station runoff with wetness values derived from satellite data (1988-2010), for expanding sub-basin stream flow information to the entire river basin where natural flow information is limited. It demonstrates the approach with flow level data that provide estimates of monthly runoff in near real time in two international river basins: Zambezi and Mekong. The paper includes an economic framework incorporating information on existing institutions to assess potential economic and political impacts and to inform policy on conflict and cooperation between riparians. The authors conclude that satellite data modeled with gauge station runoff reduce the uncertainty inherent in negotiating an international water agreement under increased hydrological variability, and thus can assist policy makers to devise more efficient institutional apparatus.